Design and Construction of a Real-Time Air Quality Monitoring System Using IoT-Based ESP32 to Strengthen Environmental Policies - Yuli Tirtariandi El Anshori; Rony Marsyal Kunda; Fredrik Manuhutu (Postgraduate, University of Mataram, 2025)
Air quality monitoring is one of the important steps in maintaining public health and the environment. With the development of Internet of Things (IoT) technology, air quality monitoring can be done in real-time and more efficiently. This study aims to environmental policy and design of an IoT-based air quality monitoring system using the ESP32 microcontroller. This system is designed to measure air quality parameters such as CO, NO2, temperature, and humidity using factory-calibrated sensors (DFRobot) connected to the ESP32 microcontroller. Data obtained from the sensors are processed by the ESP32 and sent to a cloud server via Wi-Fi, allowing real-time monitoring via the ThingSpeak platform which can be monitored via mobile devices or the web. The results of the air quality monitoring system design show that devices using electrochemical CO and NO sensors₂and the SHT30 sensor connected to the ESP32 is capable of reading and measuring CO, NOconcentrations., temperature, and humidity with good accuracy with a sample time of ± 20 seconds. In addition, this system can be connected online with the ThingSpeak platform, allowing visualization of measurement data in graphical form in real-time. Thus, the designed system not only functions optimally in detecting air quality parameters, but also supports efficient remote monitoring through Internet of Things (IoT) technology